2019
DOI: 10.12691/jfnr-7-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Examination of the Effects of Oral Consumption of Various Doses of Propolis in Mice Liver

Abstract: Introduction: Considering the widespread application of biological substances, such as Propolis, it is essential to identify the importance of its liver metabolism, its effects of the liver and safe doses. The aim of this study was to determine the histopathological effects of oral administration of Propolis on the liver in mice. Methods and materials: This study consisted of five experimental groups of male mice (25-30 g), including control, placebo and 3 treatment groups. Male mice (25-30 g). Each of the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Even though the majority of the animal studies exhibited a hepatoprotective effect of propolis, Samie-Rad et al (2014) demonstrated liver toxicity when very high doses (2000-8000 mg/kg) of propolis were given to mice [142]. The histopathological changes were dose-dependent and included central venous dilatation, steatosis, confluent necrosis, apoptosis, and focal necroinflammation [142]. However, the dose in this study was in the range of 10-40-fold that of the doses in the positive studies previously mentioned.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the majority of the animal studies exhibited a hepatoprotective effect of propolis, Samie-Rad et al (2014) demonstrated liver toxicity when very high doses (2000-8000 mg/kg) of propolis were given to mice [142]. The histopathological changes were dose-dependent and included central venous dilatation, steatosis, confluent necrosis, apoptosis, and focal necroinflammation [142]. However, the dose in this study was in the range of 10-40-fold that of the doses in the positive studies previously mentioned.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…[ [131][132][133][134][135][136][137][138][139][140][141][142] human clinical trials Reduction in hepatic steatosis severity and inflammatory markers.…”
Section: Hypertension In Vivomentioning
confidence: 99%